Exploring Accessibility of Mobile Applications Through User Feedback: Insights from App Reviews in a Systematic Literature Review - Oliveira, Alberto Dumont Alves; Eler, Marcelo Medeiros (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Mobile applications have become essential tools for daily activities, encompassing communication, productivity, and entertainment, serving a diverse user base that includes people with disabilities. Despite this broad usage, ensuring accessibility for users with varying needs remains a significant challenge. This paper presents a systematic literature review (SLR) examining the accessibility of mobile applications through user reviews. An initial search across major academic digital libraries identified 638 papers, which were narrowed down to 16 key studies published since 2013 based on specific inclusion and exclusion criteria. The articles analyzed featured a wide range of review counts, from 173 to over 179 million. Our analysis reveals various purposes, methodologies, and approaches that researchers have employed to explore digital accessibility. The SLR identifies four main strategies for collecting and analyzing accessibility reviews, with commonly referenced standards including BBC guidelines, Google Material Design, and WCAG. The results also identify persistent barriers for users with disabilities and synthesize 31 recommendations for future research directions in areas such as machine learning and the automatic extraction and classification of user reviews. These findings underscore the critical importance of integrating user feedback and perspectives into the design and development of mobile applications to ensure they are inclusive and accessible to all users.